Consumers' perspectives on their involvement in recognizing and responding to patient deterioration—Developing a model for consumer reporting. (26th December 2018) - King, Lindy; Peacock, Guy; Crotty, Mikaila; Clark, Robyn
Abstract: Background: Adverse events occur in health care. Detection and reporting of deterioration therefore have a critical role to play. Patient and family member (consumer) involvement in patient safety has gained powerful support amongst global policymakers. Few studies, with none taking a rigorous qualitative approach, have drawn upon consumers' experiences to establish their preferences in consumer reporting of patient deterioration programmes. Objective: To explore consumers' experiences of previous reporting of patient deterioration; their preferred educational strategies on this role and recommended pathways in a consumer reporting of patient deterioration model. Design, setting and participants: An interpretive, qualitative research design was utilized. Nine focus group interviews were undertaken across Adelaide, capital city of South Australia. Interviews were audio‐taped, transcribed and analysed thematically. Twenty‐six adults described, then reflected, on previous experiences of reporting patient deterioration. Results: Overarching themes incorporated consumers' experiences and patient/family education. Three themes emerged in relation to consumers' experiences: feelings, thoughts and actions. Five themes arose on educating consumers: content, timing, format, information providers and information recipients. The consumers' deep reflections on their past reporting experiences led to the development of a new model for consumer reporting of patient deterioration. Conclusions: Consumers' views on ways to improve consumer reporting of patient deterioration processes emerged. These improvements include structured educational programmes for staff advocating open health‐care professional/consumer communication, educational materials developed and tested with English‐speaking and culturally and linguistically diverse consumers and a model with three consumer reporting pathways.